Sociological survey of the current status and nature conservation in relation to the development of tourism in the cadastral of Tatranská Lomnica - Ližbetinová, Michaela (Journal for Geography, 2014)
The main part of the cadastral of Tatranská Lomnica belongs to the Tatra National Park. The activity of humans is limited there because nature is protected by law. This is the first time there will be building of new accommodation and sport facilities, especially after November 2004 when was severe wind damage in the Tatra region. In this thesis we focus on the  opinions of respondents on the current state of the environment and its protection in the municipalities of the cadastral Tatranská Lomnica in relation to the present tourist business development.
Keywords: Tatranská Lomnica cadastral; the Tatra National Park; regional development; opinions of respondents